(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Lifestyle in modern era delivers a lot of stress and due to extreme use of Guru (heavy), Madhura (sweet), Snigdha (oily), Shita (cold) Ahar and Vihar like Alashya (stationary), Adhyasana (taking another food before undigested food), Vishamashan (different timing of food) etc, people get suffer with a disease like excessive body fat or sick fat or adiposopathy. Adiposopathy leads to several metabolic diseases. Langhana upakrama (fasting) will be an effective treatment in adiposopathy. Several studies by researchers, assembled to check anatomical and pathophysiological abnormalities of adiposopathy and review of different aspects of Langhana upakrama in Samhita in perspective of metabolic disorders especially due to adiposopathy. Data study shows that on positive energy intake, accumulated subcutaneous adipose tissue, visceral adipose tissue and other fat depots can be pathogenic. This pathogenic adipose tissue causes many metabolic diseases like obesity, type 2 diabetes, hypertension, hypothyroidism, liver diseases etc. By the studies of different Samhita we can articulate that Langhana upakrama is able to bring lightness and thinness to body. Finally we can conclude that by the Langhana upakrama body uses all types of sick fat from all fat depots and it can reverse the process of adiposopathy and body becomes healthy.